Development the relationship between ESDD and the distance from the source of contaminants for the insulator - Salam, Md. Abdus; Ahmad, Hussein; Tamsir, T; S. Ahmad, Ahmad; Fuad, Syed Ahmad; Buntat, Z; M. Piah, M. A. (2000)

(untitled)
The contamination severity on the insulator surface can be expressed by equivalent salt deposit density (ESDD). The value of ESDD varies with the distance of the insulator from the source of contaminants. Normally, the main sources of contaminants affecting insulators are coming from the coastal regions, industrial areas and also deserts. The values of ESDD tend to decrease with increasing distance from the seacoast. In this paper, a relationship between the ESDD and the distance of the insulator from the source of contaminants has been derived based on dimensional analysis technique. The results obtained from the proposed relationship are compared to the other researcher's results and good agreement is observed. With this finding, effective implementation of line and station insulation coordination in contaminated conditions will be obtained